2001
DOI: 10.2214/ajr.176.3.1760641
|View full text |Cite
|
Sign up to set email alerts
|

Defecographic Measurements of Rectal Intussusception and Prolapse in Patients and in Asymptomatic Subjects

Abstract: Our findings suggest that dynamic evacuation radiology contributes to making a differential diagnosis between rectal intussusception and mucosal folds in the rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 29 publications
0
28
0
3
Order By: Relevance
“…Studies have shown that this finding is usually missed or underestimated at MR defecography because of the lack of the gravity effect and the mucosa not well depicted [47][48][49]. These are easily diagnosed by DCP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that this finding is usually missed or underestimated at MR defecography because of the lack of the gravity effect and the mucosa not well depicted [47][48][49]. These are easily diagnosed by DCP.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with RAI failing conservative treatment, surgery is considered 5,6) . Rectal intussusception (RI) has been seen in asymptomatic individuals at proctography 4) , and the clinical and pathological significance of this finding has been questioned 7) . Recent studies have addressed the differences in anorectal morphology during defecation between patients with evacuation disorder and asymptomatic individuals, and intussusception thickness was significantly greater in patients with symptomatic RI 7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Rectal intussusception (RI) has been seen in asymptomatic individuals at proctography 4) , and the clinical and pathological significance of this finding has been questioned 7) . Recent studies have addressed the differences in anorectal morphology during defecation between patients with evacuation disorder and asymptomatic individuals, and intussusception thickness was significantly greater in patients with symptomatic RI 7,8) . According to the grading system for mucosal prolapse and intussusception described by Shorvon et al 4) , noncircumferential recto-rectal infolding of 3 mm or greater is fit for grade 3, but RAI which is allocated to grade 4 or 5, is circumferential infolding.…”
Section: Introductionmentioning
confidence: 99%
“…Rectal intussusception (RI) has been seen in asymptomatic individuals at proctography [4], and the clinical and pathological significance of this finding has been questioned [7]. Recent studies have addressed the differences in anorectal morphology during defecation between patients with evacuation disorder and asymptomatic individuals, and intussusception thickness was significantly greater in patients with symptomatic RI [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have addressed the differences in anorectal morphology during defecation between patients with evacuation disorder and asymptomatic individuals, and intussusception thickness was significantly greater in patients with symptomatic RI [7,8].…”
Section: Introductionmentioning
confidence: 99%